DEVELOPMENT OF BIOINSECTICIDES AGAINST SPODOPTERA FRUGIPERDA USING CHITINOLYTIC BACTERIA: Life Sciences-Microbiology - DANAI-TAMBHALE S. D (International Journal of Life Science and Pharma Research, 2022)
Actinomycetes play an important role in the biological control of insects by producing insecticidal active compounds against various insects. They are predominantly found in soil, in the silt of water bodies, in the air and in plant remains. Chitinase is increasingly finding applications in various fields such as biomedicine, in ultra-structural studies, in the preparation of chitooligosaccharides, in single-cell protein production, biocontrol agents, agriculture, etc. Chitinase is originally an enzyme used by insects to degrade the structural polysaccharide of insects. Chitinase brings about hydrolysis of chitin which is widely distributed in cell wall of fungi, plants and insects. An attempt has been made to use chitinase producing bacteria for the development of bioinsecticides against Spodoptera frugiperda, which feeds on over more than 60 species of plants and it is periodic. The Spodoptera frugiperda armyworm (Lepidoptera) is a serious pest of cabbage and other crop. It is also major pest of maize, rice, sorghum, turf grasses, cotton, and peanuts, etc. In this attempt enrichment and isolation of chitinase producing bacteria from soil was carried out. Chitinolytic activities of the three isolates were tested against larvae of Spodoptera frugiperda. Three isolates were individually applied against Spodoptera frugiperda. The isolates named Ai, A2 and A3 were found to be more effective against Spodoptera frugiperda. The insecticidal activity of isolate A1was tested and control within 5 hours. Isolate A2 was treated with larvae Spodoptera frugiperda killed after 8 hours whereas, isolate A3 controlled after 24 hours. The evaluated insecticides provided a significant reduction in the infestation level, for variable periods.